2018
DOI: 10.7759/cureus.2163
|View full text |Cite
|
Sign up to set email alerts
|

The Fight Against Cancer: Nitrobenzaldehyde as the Potential Warrior

Abstract: New milestones have been reached in oncology with the advent of a noninvasive, photodynamic therapy which aims to eradicate cancer cells rapidly. A chemical compound, Nitrobenzaldehyde, injected into the tumor, activates by ultraviolet (UV) light and disrupts the cancer cells' internal and external dynamics. This technique could be of enormous therapeutic value in destroying numerous cancer lines including breast, prostate, pancreatic cancers, etc., without causing unwanted systemic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Hira Saleem et al [7] recently demonstrated that a chemical compound, nitro benzaldehyde when injected directly into the tumour and subjected to beam of ultraviolet (UV) light, can eliminate cancer cells from the body within two hours. The major challenges faced during the design of anticancer drugs are the drug resistance and high toxicity and hence, novel drugs with good activity and minimum toxicity are essentially required in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hira Saleem et al [7] recently demonstrated that a chemical compound, nitro benzaldehyde when injected directly into the tumour and subjected to beam of ultraviolet (UV) light, can eliminate cancer cells from the body within two hours. The major challenges faced during the design of anticancer drugs are the drug resistance and high toxicity and hence, novel drugs with good activity and minimum toxicity are essentially required in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%